مدى تطبيق الأُسس القُرآنيَّة في تكوين العلاقات الاجتماعية داخل الأُسرة الِّليبيَّة حسب وجهة نظر عينة من مشايخ ومربي الزاوية الأسمرية (Journal of Humanitarian and Applied Sciences, 2023)
Proceeding from the researcher’s specialization in social psychology, and from the importance of studying the foundations that govern and control the formation of social relations in society, the most important of which are religious and ideological foundations, and considering that the Libyan society is one of the Islamic societies that is very interested in teaching the Holy Qur’an and its sciences, which is the first pillar in the Islamic religion and it is followed by The ((Sunnah)) of the Message of Muhammad ﷺ, for this reason, the researcher turned to knowing and explaining the extent to which the Qur’anic foundations are applied in the formation of social relations within the Libyan family and the Libyan society, and he chose a sample of the sheikhs and educators of the ((Asmar zawiya )) , given that the (( Asmar zawiya )) is almost the largest Qur’anic edifice in Libya The research reached a set of results, the most important of which are:- 1- . 22 % of the sample members stated that the Quranic foundations are not used in building and forming social relationships in the Libyan family. 2- . While 13% of them answered that they sometimes use the Quranic foundations in building and forming social relations in the Libyan family. 65% of them answered that they use it often. Quranic foundations in building and forming social relations in the Libyan family.
Keywords: social psychology; Freemasonry International; Judaization